2009
DOI: 10.1016/j.watres.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition vs. enhancement of the nitrate-induced phototransformation of organic substrates by the •OH scavengers bicarbonate and carbonate

Abstract: Contrary to common expectations, the hydroxyl scavengers, carbonate and bicarbonate, are able to enhance the phototransformation by nitrate of a number of substituted phenols. Carbonate and bicarbonate, in addition to modifying the solution pH, are also able to induce a considerable formation of the carbonate radicals upon nitrate photolysis. The higher availability of less-reactive species than the hydroxyl radical would contribute to substantially enhance the photodegradation of the phenols/phenolates that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…Direct photolysis, reaction with • OH and other transient species, and nitration are possible transformation pathways in paddyfield water (Armbrust 1999;Chiron et al 2009). Nitroderivatives like 2N4CP absorb a larger fraction of sunlight compared with 4CP, but they have lower quantum yields for the direct photolysis (Vione et al 2009). Additionally, the nitro group is expected to decrease the reaction rate constants with • OH and other transient species (Neta et al 1988;Minero et al 2006), and would inhibit further nitration processes (Machado and Boule 1995;Dzengel et al 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct photolysis, reaction with • OH and other transient species, and nitration are possible transformation pathways in paddyfield water (Armbrust 1999;Chiron et al 2009). Nitroderivatives like 2N4CP absorb a larger fraction of sunlight compared with 4CP, but they have lower quantum yields for the direct photolysis (Vione et al 2009). Additionally, the nitro group is expected to decrease the reaction rate constants with • OH and other transient species (Neta et al 1988;Minero et al 2006), and would inhibit further nitration processes (Machado and Boule 1995;Dzengel et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…They modify the pH of the solution, consume the • OH radicals produced upon irradiation of nitrate and nitrite, and enhance the generation of the radicals CO 3 −• (Chiron et al 2009a). The overall effect is strongly substrate-dependent (Vione et al 2009). The formation of 2N4CP as a secondary pollutant is of concern because this compound is refractory to biological degradation, and it is toxic to organisms (The Merck Index 2006).…”
Section: Background Aim and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. Data concerning lagoon water in the Rhône delta (Chiron et al, 2007) and water in Lake Candia (Vione et al, 2009d Captions to the Figures Figure 1. Absorption spectra (molar absorption coefficients ε) of MCPA at pH 1.8 and 7.7, adjusted by addition of HClO 4 and NaOH, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the reactivity between organic compounds and CO 3 −• can be carried out with a semi-quantitative screening method, which makes use of nitrate and bicarbonate under UVB irradiation (Vione et al, 2009). The application of this method (see SM) suggested that the reaction between BP-3 and CO 3 −• might possibly be important, which prompted us to use the laser flash photolysis technique to get insight into reaction kinetics.…”
Section: Reaction With Co 3 −•mentioning
confidence: 99%